VD_FINDINFO Jug / 2015 / 151 vom 10. November 2014 - VD Tribunal cantonal (2014)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, RÉSILIATION IMMÉDIATE, RÉSILIATION ABUSIVE | 337 CO, 337b CO, 337c CO, 14 LPers-VD, 16 LPers-VD, 2 al. 1 LPers-VD, 41 LPers-VD, 61 LPers-VD